Peran Guru Pendidikan Agama Islam dalam Membina Kepatuhan Berpakaian Islami Siswa di SMP Negeri 1 Batang Natal - Maya Sari; Rosdialena R (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study was motivated by the persistence of students' non-compliance with Islamic dress regulations at SMP Negeri 1 Batang Natal, including excessive use of lipstick, improper wearing of the hijab, failure to wear an underscarf resulting in visible hair, and untidy appearance among male students. These conditions indicate that students' compliance with dress regulations is not yet fully based on personal awareness but is still influenced by teacher supervision. This study aims to describe the forms of students' non-compliance with Islamic dress codes, analyze the role of Islamic Religious Education (PAI) teachers in fostering compliance with Islamic dress regulations, and identify the supporting and inhibiting factors in the guidance process. This study employed a qualitative approach with a descriptive research design. Data were collected through observations, interviews, and documentation involving PAI teachers, the principal, homeroom teachers, and students. Data were analyzed through data reduction, data presentation, and conclusion drawing. The findings revealed that PAI teachers play roles as educators, role models, mentors, supervisors, and motivators in fostering students' compliance with Islamic dress codes. The guidance was carried out through religious instruction, advice, habituation, supervision, and collaboration with parents and school authorities. Supporting factors included school regulations, a religious school environment, institutional support, and parental involvement. Inhibiting factors included low student awareness, peer influence, fashion trends, social media exposure, and limited family supervision. Continuous guidance contributes to the development of students' awareness to dress in accordance with Islamic values.